Pengaruh Kompensasi Dan Lingkungan Kerja Terhadap Kinerja Guru Taman Kanak-Kanak Jakarta Timur - alimudin alimudin (Qiro'ah : Jurnal Pendidikan Agama Islam, 2019)
This study aims to determine the compensation contributor to teacher performance, the influence of work environment on teacher performance, and the influence of interaction between the two on teacher performance. This research uses Expost Facto research method. With research populations in eastern Jakarta. Of the total population of 566 teachers with sample sampling using the technique of custer rendom sampling (sampling area) with 10% significant number of samples amounted to 264 samples. The result of this research shows that (a). there is a significant influence between compensation and work environment, (b). there is significant influence between environment on teacher performance, and (c) there is interaction between compensation and work environment to teacher performance in east Jakarta area.